Development of a Competitive and Collaborative Platform for Block Diagram and Resistive Circuit Reduction in a Basic Electrical Engineering Course - Ayodele, Obasegun, Tekena (My University, 2018)
Competition and collaboration are two universal ingredients in all human cultures. Competition has been observed over time as a phenomenon that has helped people achieve the very best of their potentials in their various fields. Competition has also helped individuals achieve feats they would not have ordinarily achieved as they are pushed beyond their limits. The same can also be said of cooperation and collaboration, which can be used to achieve specific goals or objectives. Hence, both competition and collaboration can be vital in creating a healthy learning process among students. This paper discusses a competitive and collaborative platform on the learning process for two selected online courses in Electrical Engineering. Using a platform developed in LabVIEW programming language, a community of students were encouraged to compete online as they try to reduce block diagrams of subsystems in Control Engineering as well as reduce given Series-Parallel Resistor Circuits in the shortest time and amount of steps possible. At the end of each trial, students can view the finish time of other students and can share, online, their individual solutions with the community as well as discuss ideas such as reduction techniques they find most expedient via a public online notepad. This creates a means of learning from the community. The platform helps to passively induce a competitive and collaborative perspective in the learning pathway of students, thereby improving the interest and experience of students in the selected subject areas. The platform uses an online server to maintain communications from all the students in their various locations. Students can view the timed performance of their counterparts on a leadership board thereby engendering induced competition in the learning community. The instructor or administrator can also monitor activities in the community from a server portal.
Supplemental Materials: https://osf.io/6tpe5/
Keywords: competition; collaboration; Electrical Engineering; Block Diagrams; reduction; LabView